Kinetic Glomerular Filtration Rate Equations in Patients With Shock: Comparison With the Iohexol-Based Gold-Standard Method. Issue 8 (12th March 2021) - Desgrouas, Maxime; Merdji, Hamid; Bretagnol, Anne; Barin-Le Guellec, Chantal; Halimi, Jean-Michel; Ehrmann, Stephan; Salmon Gandonnière, Charlotte
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: Static glomerular filtration rate formulas are not suitable for critically ill patients because of nonsteady state glomerular filtration rate and variation in the volume of distribution. Kinetic glomerular filtration rate formulas remain to be evaluated against a gold standard. We assessed the most accurate kinetic glomerular filtration rate formula as compared to iohexol clearance among patients with shock. DESIGN: Retrospective multicentric study. SETTING: Three French ICUs in tertiary teaching hospitals. PATIENTS: Fifty-seven patients within the first 12 hours of shock. MEASUREMENTS AND MAIN RESULTS: On day 1, we compared kinetic glomerular filtration rate formulas with iohexol clearance, with or without creatinine concentration correction according to changes in volume of distribution and ideal body weight. We analyzed three static glomerular filtration rate formulas (Cockcroft and Gault, modification of diet in renal disease, and Chronic Kidney Disease–Epidemiology Collaboration), urinary creatinine clearance, and seven kinetic glomerular filtration rate formulas (Jelliffe, Chen, Chiou and Hsu, Moran and Myers, Yashiro, Seelhammer, and Brater). We evaluated 33 variants of these formulas after applying corrective factors. The bias ranged from 12 to 47 mL/min/1.73 m 2 . Only the Yashiro equation had a lower bias than urinary creatinine clearance before applying corrective factors (15 vs 20 mL/min/1.73 m 2 ). The corrected Moran and Myers formula had the best mean bias, 12 mL/min/1.73 m 2, but wide limits of agreement (–50 to 73). The corrected Moran and Myers value was within 30% of iohexol-clearance–measured glomerular filtration rate for 27 patients (47.4%) and was within 10% for nine patients (15.8%); other formulas showed even worse accuracy. CONCLUSIONS: Kinetic glomerular filtration rate equations are not accurate enough for glomerular filtration rate estimation in the first hours of shock, when glomerular filtration rate is greatly decreased. They can both under- or overestimate glomerular filtration rate, with a trend to overestimation. Applying corrective factors to creatinine concentration or volume of distribution did not improve accuracy sufficiently to make these formulas reliable. Clinicians should not use kinetic glomerular filtration rate equations to estimate glomerular filtration rate in patients with shock.